The effect of branding on consumer palatability ratings of beef strip loin steaks - Wilfong, Alaena K.; McKillip, Kassandra V.; Gonzalez, John M.; Houser, Terry A.; Unruh, John A.; Boyle, Elizabeth A.E.; O'Quinn, Travis G. (My University, 2017)
The objective of this study was to determine the influence of knowing the brand or USDA grade on consumer palatability ratings of beef strip loin steaks. Strip loins were selected to represent 5 USDA grades and brands, USDA Select, Choice, Prime, Certified Angus Beef (CAB; upper 2/3 Choice), and Select, from carcasses of cattle classified as Angus on the basis of phenotype. After 21 d of aging, 2.5-cmthick steaks were cut, consecutively cut steaks were paired for consumer evaluation. Consumer panelists (n = 112) evaluated samples for tenderness, juiciness, flavor liking, and overall liking. Additionally, consumers rated each palatability trait as either acceptable or unacceptable. Samples were fed in 2 rounds on the same day: blind and informed testing. In the first round, blind testing, consumers were served 1 sample from each treatment, with no product information provided. In the second round, consumers were informed of the brand or quality grade prior to sampling. During blind testing, CAB rated similar (P > 0.05) to Choice for all palatability traits; however, CAB rated greater P < 0.05) than Choice for all traits during informed testing. Additionally, Angus Select and Select were rated similar (P > 0.05) for all traits when tested blind, but Angus Select was rated greater (P < 0.05) than Select for flavor and overall liking when brand was declared. When comparing blind and informed ratings, Angus Select and CAB had greater (P < 0.05) ratings for juiciness, flavor liking, and overall liking, and Prime had increased (P < 0.05) ratings for flavor liking and overall liking because of brand disclosure. However, ratings for Choice and Select samples were unaffected (P > 0.05) when brand was disclosed. Brand knowledge increased (P < 0.05) the percentage of Prime samples rated as acceptable for flavor and the percentage of Angus Select samples rated as acceptable for flavor and overall liking. Conversely, there was no difference (P > 0.05) in the percentage of Choice and Select samples rated as acceptable for all palatability traits. These data indicate that Prime, CAB, and Angus Select steaks receive an increase in consumer palatability perception, or "brand lift," which does not occur for Choice and Select beef.
Citation: Wilfong, A. K., McKillip, K. V., Gonzalez, J. M., Houser, T. A., Unruh, J. A., Boyle, E. A. E., & O'Quinn, T. G. (2016). The effect of branding on consumer palatability ratings of beef strip loin steaks. Journal of Animal Science, 94(11), 4930-4942. doi:10.2527/jas2016-0893
Keywords: Angus; Beef; Branding; Consumer; Marbling; Palatability